DIP2B Interacts With α-Tubulin to Regulate Axon Outgrowth - Xing, Zhen-Kai; Zhang, Lu-Qing; Zhang, Yu; Sun, Xue; Sun, Xiao-Lin; Yu, Hua-Li; Zheng, Yao-Wu; He, Zi-Xuan; Zhu, Xiao-Juan (Frontiers in Cellular Neuroscience, 2020)
Axonal development is essential to the establishment of neuronal morphology and circuitry, although the mechanisms underlying axonal outgrowth during the early developmental stages remain unclear. Here, we showed that the conserved disco-interacting protein B (DIP2B) which consists of a DMAP1 domain and a crotonobetaine/carnitine CoA ligase (Caic) domain, is highly expressed in the excitatory neurons of the hippocampus. DIP2B knockout led to excessive axonal outgrowth but not polarity at an early developmental stage. Furthermore, the loss of DIP2B inhibited synaptic transmission for both spontaneous and rapid release in cultured hippocampal neurons. Interestingly, DIP2B function during axonal outgrowth requires tubulin acetylation. These findings reveal a new conserved regulator of neuronal morphology and provide a novel intervention mechanism for neurocognitive disorders.